Salivary gland morphology, tissue tropism and the progression of tospovirus infection in Frankliniella occidentalis - Montero Astúa, Mauricio (2016)
Tomato spotted wilt virus (TSWV) is transmitted by thrips in a propagative manner; however, progression of virus infection in the insect is not fully understood. The goal of this work was to study the morphology and infection of thrips salivary glands. The primary salivary glands (PSG) are complex, with three distinct regions that may have unique functions. Analysis of TSWV progression in thrips revealed the presence of viral proteins in the foregut, midgut, ligaments, tubular salivary glands (TSG), and efferent duct and filament structures connecting the TSG and PSG of first and second instar larvae. The primary site of virus infection shifted from the midgut and TSG in the larvae to the PSG in adults, suggesting that tissue tropism changes with insect development. TSG infection was detected in advance of PSG infection. These findings support the hypothesis that the TSG are involved in trafficking of TSWV to the PSG.